Experimental investigation and mechanical model for assembled joints of prefabricated two-wall-in-one diaphragm walls. (15th January 2023) - Qiu, Tong; Zhang, Jiqing; Chen, Xiangsheng; Xu, Zhenyan; Su, Dong; Song, Ran; Cui, Tao
Highlights: Prefabricated two-wall-in-one diaphragm wall is a new green product. Full-scale pure bending experiments were conducted on joint and wall specimens. Welded joint is no more a weak link in prefabricated components. Fastener mechanism is significant to exert the highest joint performance. A joint model is validated by experiment and accurately presents joint performance. Abstract: The cast-in-place construction of diaphragm wall with problems of high consumption, low quality, high risk and pollution is difficult to meet the requirements of low-carbon city development. To overcome this problem, this study demonstrates the first application of prefabricated two-wall-in-one diaphragm wall and its key assembled joint model in Shenzhen Metro Line 8 subway station. First, this study conducted a full-scale pure bending experimental study on joint and wall specimens of prefabricated two-wall-in-one diaphragm wall. A comparative study of the experimental responses was conducted. Second, the mechanical model for assembled joint was proposed. Third, model validation and assessment was performed with experimental data. The main conclusions include: (1) The axial force was beneficial in restraining the cracks and openings of the joint specimen. Joint deformation does not conform to the plane hypothesis, but is related to interface contact and fastener constraint. (2) None of the interfaces of welded joint separated during failure phase. The bearing capacity of welded joint is 91.67% higher than that of adjacent continuous sections and is no longer a weak link. (3) Welded joint guarantees steady stiffness decline and good ductility of prefabricated two-wall-in-one diaphragm wall. (4) The model assessment indicates that the fastener mechanism is significant to exert the highest mechanical properties of assembled joints. Notably, prefabricated two-wall-in-one diaphragm walls represent a green product for low-carbon, high-quality urban development. The proposed model provides significant convenience and practical value for the application of novel assembled joints and the promotion of green products.